Development of a web-based toolkit to support improvement of care coordination in primary care. Issue 3 (23rd May 2018) - Ganz, David A; Barnard, Jenny M; Smith, Nina Z Y; Miake-Lye, Isomi M; Delevan, Deborah M; Simon, Alissa; Rose, Danielle E; Stockdale, Susan E; Chang, Evelyn T; Noël, Polly H; Finley, Erin P; Lee, Martin L; et al.
Abstract: Promising practices for the coordination of chronic care exist, but how to select and share these practices to support quality improvement within a healthcare system is uncertain. This study describes an approach for selecting high-quality tools for an online care coordination toolkit to be used in Veterans Health Administration (VA) primary care practices. We evaluated tools in three steps: (1) an initial screening to identify tools relevant to care coordination in VA primary care, (2) a two-clinician expert review process assessing tool characteristics (e.g. frequency of problem addressed, linkage to patients' experience of care, effect on practice workflow, and sustainability with existing resources) and assigning each tool a summary rating, and (3) semi-structured interviews with VA patients and frontline clinicians and staff. Of 300 potentially relevant tools identified by searching online resources, 65, 38, and 18 remained after steps one, two and three, respectively. The 18 tools cover five topics: managing referrals to specialty care, medication management, patient after-visit summary, patient activation materials, agenda setting, patient pre-visit packet, and provider contact information for patients. The final toolkit provides access to the 18 tools, as well as detailed information about tools' expected benefits, and resources required for tool implementation. Future care coordination efforts can benefit from systematically reviewing available tools to identify those that are high quality and relevant. Abstract : With input from clinicians and patients, 18 primary care-focused care coordination tools (from among 300) were posted to a Veterans Affairs website for primary care teams to use for improvement projects.